2005
DOI: 10.1159/000086825
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Atrial Natriuretic Peptide in Fetuses with Cardiac Disease

Abstract: Objective: To investigate atrial natriuretic peptide (ANP) levels in fetuses with cardiac defects and to evaluate the relationships between plasma ANP levels and the presence of polyhydramnios. Methods: Plasma ANP levels were measured by radioimmunoassay in 27 fetuses with cardiac abnormalities and in 14 normal healthy fetuses. Results: Fetal plasma ANP levels were similar in the two studied groups (p = 0.18) but they were significantly higher in a subset of cases with cardiac disease and polyhydramnios (n = 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…While Zeevi et al reported a significant increase of ANP in PS, AS, CoA and MS compared to controls, Matsuoka et al and Yeh et al could not confirm this (13, 23, 25). By examining whether fetuses with cardiac malformations already show increased ANP levels, different types of CHD did not significantly differ (19). Furthermore, no significant difference to fetal controls could be detected.…”
Section: Anp In Pediatric Heart Failurementioning
confidence: 99%
“…While Zeevi et al reported a significant increase of ANP in PS, AS, CoA and MS compared to controls, Matsuoka et al and Yeh et al could not confirm this (13, 23, 25). By examining whether fetuses with cardiac malformations already show increased ANP levels, different types of CHD did not significantly differ (19). Furthermore, no significant difference to fetal controls could be detected.…”
Section: Anp In Pediatric Heart Failurementioning
confidence: 99%